The use of open management practices and their impact on expanding the tax base Applied research at the General Commission for Taxes (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The research aims the impact of the relationship between the independent variable president (open management)and the dimensions of (sharing information, training and development, empowerment, motivation), adoptedvariable (expanding tax base) dimensions of (reduction of tax evasion, Facilitate procedures, voluntary compliance of tax, tax collection, tax awareness) and the degree of the order of dimensions according to their significance, as well as a statement of moral differences in the surveyed sample response according to personal variables of (age, educational qualification, job site, the number of years of service), it has been adopted the descriptive approach analytical using the questionnaire as a tool head of the data and information collected from the sample of (126) Officials represented by functional sites (m. Director General, Department Director, Deputy Director of the first division, Deputy Director of the second division, Division official, Assistant Division Administrator) in the General Authority for taxes in Baghdad, as well as for conducting personal interviews with officials The answers were analyzed depending on the statistical program ) SPSS V.18 ( In calculating ) the weighted arithmetic mean, standard deviation, coefficient of variation, simple linear regression analysis, test f, Coefficient of determination R 2( And highlighted the results of the research are: the existence of a relationship effect positive of moral of a statistically significant for the open management style in expanding the tax base  .